The effects of heat treatment on the microstructure and mechanical properties of cold spraying additive manufacturing Ti - Zhipo Zhao; Yidi Wang; Jiqiang Wang; Tianying Xiong; Xinyu Cui (Journal of Materials Research and Technology)
Cold spraying additive manufacturing (CSAM) Ti exhibits minimal plasticity, posing a significant challenge to its broader application. Heat treatment is recognized as a potent strategy to enhance the mechanical properties of additive manufacturing parts. However, prior investigations have struggled to discern the genuine impact of heat treatment on CSAM Ti due to the high porosity in initial deposits. This study addresses this gap by fabricating CSAM Ti deposits with a low porosity of 2.76 %. The effects of annealing at varies temperature on the microstructure, porosity, and mechanical properties of the deposits were studied. The results show that annealing can promote recrystallization of CSAM Ti and reduce the porosity of CSAM Ti until to 0.77 %. This increases the strength of CSAM Ti to 780 MPa, which even exceeds that of wrought pure Ti. Despite the low elongation of 4.67 %, the CSAM Ti after suitable heat treatment can be used in fields in fields don't require high plasticity.